2016
DOI: 10.1007/s12011-016-0819-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 22 Elements in Milk, Feed, and Water of Dairy Cow, Goat, and Buffalo from Different Regions of China

Abstract: The objectives of this study were to measure the concentrations of elements in raw milk by inductively coupled plasma-mass spectrometry (ICP-MS) and evaluate differences in element concentrations among animal species and regions of China. Furthermore, drinking water and feed samples were analyzed to investigate whether the element concentrations in raw milk are correlated with those in water and feed. All samples were analyzed by ICP-MS following microwave-assisted acid digestion. The mean recovery of the elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 30 publications
(46 reference statements)
6
24
4
3
Order By: Relevance
“…As (μg/L) Cd (μg/L) differences observed between these results and the studies by Tang et al (2014) and Zhou et al (2016) who also conducted studies in China. As mentioned previously, the results obtained by Tang et al (2014) from Chinese regions showed similar values for Pb and higher values for Cd.…”
Section: Pb (μG/l)contrasting
confidence: 83%
See 4 more Smart Citations
“…As (μg/L) Cd (μg/L) differences observed between these results and the studies by Tang et al (2014) and Zhou et al (2016) who also conducted studies in China. As mentioned previously, the results obtained by Tang et al (2014) from Chinese regions showed similar values for Pb and higher values for Cd.…”
Section: Pb (μG/l)contrasting
confidence: 83%
“…Area J showed an extremely high variability for Cd content which can relate to the higher value observed by Tang et al (2014) from a lower number of samples. Zhou et al (2016) observed a higher positive rate for As (82.5%) and a lower rate for Cd (32.5%). In Zhou et al (2016), only 40 raw cow milk samples were collected in two regions (20 samples per region instead of 100 in the present study).…”
Section: Pb (μG/l)mentioning
confidence: 81%
See 3 more Smart Citations